Duties and Functions of a Professional Teacher at Madrasah Ibtidaiyah (MI) Pandanaran Yogyakarta - Aisyah, Dewi Siti; Putri, Ayu Marshela; Al-Ulya, M. Nailu Syifa; Hayani, Aida (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
In the world of education,the duites and functions of a professional teacher are very important, because an experienced teacher has big duties and responsibilities, namely to motivate, educate, facilitate and train students. Education is an important thing to prepare for the future ,with that in education requires effective learning and also requires professional teachers in order to achieve the desired goals.The research is a type of qualitative research taking the background of MI Pandanaran Yogyakarta.Date collection was carried out by conducting observations,interviews and documentation.From the results of out research it shows that the duties and functions of a professional teacher greatly influence students. Meanwhile according to the principal at MI Pandanaran as a professional principal, that is, always overseeing the course of learning at school and taking part in tasks in the administration section. Meanwhile. according to one teacher at MI Pandanaran, a professional teacher must be able to convey material and condition students and always upgrade themselves so that the material presented is not monotonous and always keeps up with the times.